Perancangan Strategi Pemeliharaan Engine C32 Berbasis Fishbone Diagram, FMEA, dan RCM untuk Peningkatan Umur Pakai pada PT XYZ - Nurizal Deo Fandi; Agung Widiyanto Fajar S.; Bekti Nugrahadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The reliability of Caterpillar C32 engines plays a crucial role in maintaining the productivity of heavy equipment operations at PT XYZ. However, 21 out of 105 engines experienced premature failure before reaching the company's targeted service life, resulting in increased downtime and maintenance costs. This study aims to develop a maintenance strategy to improve the reliability and service life of Caterpillar C32 engines. A quantitative descriptive approach was employed using historical failure data collected from January 2023 to July 2025. The analysis consisted of root cause identification using the Fishbone Diagram, risk assessment through Failure Mode and Effects Analysis (FMEA), and maintenance strategy development using Reliability Centered Maintenance II (RCM II). The results showed that approximately 90% of engine failures were caused by engine seizure due to hydraulic lock resulting from cooling system failures. The FMEA identified fan motor damage as the highest-priority failure mode with a Risk Priority Number (RPN) of 576, followed by radiator clogged and aftercooler clogged, each with an RPN of 405. Based on the RCM II analysis, the proposed maintenance strategy consists of condition-based maintenance for components with measurable operating conditions and scheduled replacement for components exhibiting age-related failure patterns. The initial implementation increased engine service life from approximately 22,456–25,894 operating hours to 28,120–29,450 operating hours, bringing it closer to the company's target of 30,000 operating hours.